2014
DOI: 10.1213/ane.0000000000000250
|View full text |Cite
|
Sign up to set email alerts
|

A Simulator Study of Tube Exchange with Three Different Designs of Double-Lumen Tubes

Abstract: The Fuji-Phycon DLT was easier to pass over an AEC in this simulator trial and warrants consideration in patients with difficult airways who require 1-lung ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…We recruited 33 publications demonstrating the use of different VL for placement of DLT. [ 5 7 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We recruited 33 publications demonstrating the use of different VL for placement of DLT. [ 5 7 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 ]…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the type of DLT design can play a role in facilitating the placement of DLT over an AEC using a GlideScope ® . [ 10 ] The Fuji-Phycon DLT (Silbroncho ® , Fuji Systems, Tokyo, Japan) was found to be easier to pass over an AEC compared with both the Rusch (Bronchopart ® , Teleflex, Research Triangle Park, NC) and Mallinckrodt (Broncho-Cath ® , Covidien, Mansfield, MA) DLT warrants consideration in patients with difficult airway [ Table 1 ]. [ 10 ] The flexibility and the 45° angulated distal bevel of the reinforced bronchial lumen of the Fuji-Phycon DLT can potentially facilitating passage of the DLT into the glottis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, previous works showed that adjunct laryngoscopy for this procedure may assist with not only continuous glottis viewing, but also clearing the pathway for AEC (16). In fact, adjunct video laryngoscopy may result in better glottis viewing and fewer airway complications (16,17). If resistance of AEC is encountered during removing a DLT, as in this patient, performing adjunct video laryngoscopy to inspect the paraglottic structures during this procedure is necessary.…”
Section: Discussionmentioning
confidence: 99%